Percepção dos gestores de saúde sobre o Centro de Referência em Saúde do Trabalhador – CEREST - Dias, Renata Cristina Sobral [UNESP] (Universidade Estadual Paulista (Unesp), 2010)
A Rede Nacional de Atenção Integral à Saúde do Trabalhador (RENAST), conforme definida pelo Ministério da Saúde, é uma rede desenvolvida de forma articulada entre o Ministério da Saúde, as Secretarias de Saúde dos Estados, do Distrito Federal e dos Municípios. Tem como objetivo articular, no âmbito do SUS, ações de prevenção, promoção e recuperação da saúde dos trabalhadores urbanos e rurais, independentemente do vínculo empregatício e tipo de inserção no mercado de trabalho. Esta estratégia está sendo implementada por Centros de Referência em Saúde do Trabalhador (CEREST), que tem como função suporte técnico, educação permanente, coordenação de projetos de assistência, promoção e vigilância à saúde dos trabalhadores, no âmbito da sua área de abrangência. Esse estudo possibilita fazer uma reflexão entre o trabalho prescrito e o trabalho real dessa Instância. Nesse contexto, nosso objetivo geral é verificar a percepção dos gestores de saúde da área de abrangência do CEREST de Presidente Prudente SP, sobre a importância deste para região. Os objetivos específicos que nortearam essa pesquisa são: verificar qual o conceito de saúde do trabalhador na percepção dos gestores da área de abrangência do CEREST/PP; avaliar como os gestores de diferentes instâncias de saúde percebem o papel de CEREST; possibilitar reflexões sobre a atuação dos gestores da área de abrangência do CEREST; identificar dificuldades no desenvolvimento do papel destes profissionais no cotidiano do trabalho; e, contribuir para o fortalecimento das ações em saúde do trabalhador. Sobre as questões metodológicas, as etapas de nossa investigação seguiram procedimentos de abordagem quanti-qualitativa...

The National Network for Comprehensive Health Care Workers (RENAST) as defined by the Health Ministry, is a network developed jointly between the Ministry of Health, the Departments of Health, the Federal District and Municipalities. Aims to articulate within the SUS, prevention, health promotion and rehabilitation of urban and rural workers, regardless of the employment relationship and type of insertion in the labor market. This strategy is being implemented by the Reference Centers in Occupational Health (CEREST), which has as its technical support, continuing education, coordination of assistance projects, promotion and health surveillance of workers in its service area. This study allows to reflect between prescribed work and real work in this instance. In this context, our main objective is to verify the design of the health managers of the area covered by the CEREST Presidente Prudente SP, on the importance for this region. The specific objectives that guided this research is to verify that the concept of occupational health in the perception of managers of the coverage area of CEREST / PP; assess how managers of different health authorities perceive the role of CEREST; possible reflections on the role managers of the area covered by the CEREST; identify issues impeding development of the role of these professionals in daily work, and contribute to the strengthening of actions on workers' health. On methodological issues, the steps of our research procedures followed quanti-qualitative approach. We make use of two instruments at two different times to collect data: self-administered questionnaire and semidirected. The subjects of the questionnaire twenty managers, representatives of the Boards... (Complete abstract click electronic access below)
Keywords: Politicas publicas; Trabalhos - aspectos psicológicos; Sistema Único de Saúde (Brasil); National Network of Integral Attention to Health Worker; Reference Center for Ocuppational Health; Health Manager